1978
DOI: 10.1080/21548331.1978.11707358
|View full text |Cite
|
Sign up to set email alerts
|

When Cholecystectomy?

Abstract: The crux of the matter is to avoid being forced into cholecystectomy when the patient is acutely ill and has an increased risk of operative mortality. The rationale for performing surgery on an elective basis in patients with chronic gallbladder disease and for early medical management in most patiens with acute disease is discussed, along with the specifics of diagnosis and special considerations in the handling of problem cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…[1] The announcement of the formation of a new company, Cargill Dow LLC, in 1997 brought two large companies together to focus on the production and marketing of PLA with the intention of significantly reducing the cost of production and making PLA a large-volume plastic. [2] PLA can be prepared by both direct condensation of lactic acid and by the ring-opening polymerization of the cyclic lactide dimer (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…[1] The announcement of the formation of a new company, Cargill Dow LLC, in 1997 brought two large companies together to focus on the production and marketing of PLA with the intention of significantly reducing the cost of production and making PLA a large-volume plastic. [2] PLA can be prepared by both direct condensation of lactic acid and by the ring-opening polymerization of the cyclic lactide dimer (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…1 The development of effective methods for the production of lactic acid from biomass, therefore, has been of great industrial interest. 2,3 Although the fermentation of dextrose using lactic acid bacilli is currently practiced in industry to produce lactic acid, [4][5][6] biological processes, in general, have various drawbacks: low reaction rates causing long reaction times and huge reactors, low concentrations of products usually in water solutions ending up with high energy consumptions for their separations, and so on. The chemical methods for producing lactic acid 7,8 or its esters 9,10 reported so far, on the other hand, have not yet been put into practice for some specific reasons.…”
mentioning
confidence: 99%
“…The inhibitor and catalyst are custom loaded and introduced in‐line with specialized feeder equipment. [ 67 ] It has been reported that this system allows the optimization of the cure speed and temperature by varying the catalyst and inhibitor loading at the injection molding machine. [ 67 ]…”
Section: Processingmentioning
confidence: 99%